2003
DOI: 10.4049/jimmunol.170.5.2680
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Secretion of Monocyte Chemotactic Protein-1 Stimulated by the High Affinity Receptor for IgE

Abstract: In prior studies aggregation of the high affinity receptors for IgE, FcεRI, on a rat mast cell line, RBL-2H3, stimulated transcription of the gene for monocyte chemotactic protein-1 (MCP-1) and secretion of the protein. Unexpectedly, those delayed events appeared much less constrained by kinetic proofreading than had been documented for other receptor-initiated responses. The results of the present experiments are consistent with the proposal that the biosynthesis and secretion of MCP-1 result from a soluble m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…We investigated the effect of the flavonoids on the release of CCL2 because it is known to be synthesized by MC 13 and it stimules recruitment of immune cells to the site of inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated the effect of the flavonoids on the release of CCL2 because it is known to be synthesized by MC 13 and it stimules recruitment of immune cells to the site of inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…While luteolin had been reported to inhibit histamine release from hCBMCs 30 this is the first time that lut and methlut are reported to inhibit CCL2 release. CCL2 is known to be synthesized by MC 13 and stimulates recruitment of immune cells to the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that abnormal increases in IgE levels after treatment of TMA were significantly suppressed by oral administration of PFE, whereas PS treatment had no such effect ( Figure 3A). MCP-1 synthesis and secretion has been found to be closely related to IgE expression (Eglite et al, 2003). Thus, we sought to determine whether PFE affects MCP-1 expression.…”
Section: Effect Of Pfe On Tma-induced Ige Mmcp-1 and Il-1β Productimentioning
confidence: 99%
“…A model explaining this escape has been proposed that involves the formation of a messenger that spreads the signal beyond the initial signaling complex containing the ligand and receptor (8,9). In the case of MCP-1, a gene for which transcriptional activation appears to escape kinetic proofreading in RBL-2H3 cells, several experiments have been interpreted as supporting the hypothesis that calcium ions (Ca 2ϩ ) released from intracellular stores may serve as the messenger that allows escape (10). Transcriptional activation of other chemokines also appears to escape kinetic proofreading through similar mechanisms (6).…”
mentioning
confidence: 98%